2020
DOI: 10.3390/membranes10100284
|View full text |Cite
|
Sign up to set email alerts
|

Forward Osmosis as Concentration Process: Review of Opportunities and Challenges

Abstract: In the past few years, osmotic membrane systems, such as forward osmosis (FO), have gained popularity as “soft” concentration processes. FO has unique properties by combining high rejection rate and low fouling propensity and can be operated without significant pressure or temperature gradient, and therefore can be considered as a potential candidate for a broad range of concentration applications where current technologies still suffer from critical limitations. This review extensively compiles and critically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 254 publications
(325 reference statements)
0
21
0
Order By: Relevance
“…OM applications can use different types of saline water, which may contain sparingly soluble ions and impurities with high concentrations. For example, in desalination-hybrid processes where seawater or seawater desalination brine is used, a great amount of scaling precursors like Ca 2+ , Mg 2+ , SO 4 2− , and CO 3 2− exist [54]. Sparingly soluble salts may precipitate and deposit on membrane during operation.…”
Section: Anti-scaling Performance Of Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…OM applications can use different types of saline water, which may contain sparingly soluble ions and impurities with high concentrations. For example, in desalination-hybrid processes where seawater or seawater desalination brine is used, a great amount of scaling precursors like Ca 2+ , Mg 2+ , SO 4 2− , and CO 3 2− exist [54]. Sparingly soluble salts may precipitate and deposit on membrane during operation.…”
Section: Anti-scaling Performance Of Membranesmentioning
confidence: 99%
“…Niche applications using DSs without the need of regeneration (e.g., seawater [ 1 ], desalination brine [ 2 ], or fertilizer solutions [ 3 ]) are attractive due to the elimination of energy-intensive DS re-concentration step. OM and hybrid OM processes have been explored for diverse fields [ 4 ], such as wastewater reuse [ 5 , 6 , 7 ], desalination [ 8 , 9 , 10 , 11 ], osmotic membrane bioreactor [ 12 ], energy production [ 13 , 14 , 15 ], and food processing [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the performance of the FO system is associated with many factors, including FO membrane properties, areas of application, and operation conditions. Although there are a number of comprehensive reviews reported in recent years, they mainly focus on the fabrication and modification methods of FO membranes [ 30 ], the utilisation of FO membranes for desalination [ 31 ], and the concentration process [ 32 ]. In this work, we aim to provide a concise review of the latest development of applying FO technology for sewage concentration and wastewater treatment and focus on the interaction among membrane materials, feed solution properties, draw solution properties, and system operating conditions during the application.…”
Section: Introductionmentioning
confidence: 99%
“…It emerges with its distinctive advantages of lower pollution tendency, higher resilience after cleaning and lower energy consumption than conventional pressure-driven membrane technologies. FO technology has shown intriguing potentials in various application fields, such as desalination, wastewater treatment, food and drug concentration, and power generation [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%